Hermeneutika Gadamer Sebagai Teknik Analisi Pesan Dakwah - Prihananto, Prihananto (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
This article discusses Gadamer's hermeneutics to understand and analyse the messages of Da’wa, including the rational importance of interconnection and integration between hermeneutic theories developed in the West and in Islamic world, especially regarding to the message of Da’wa in Islamic communication. In addition, the principal key issues to be addressed in this article are related to how the development of hermeneutic itself. The author argues that Gadamer's hermeneutics Ricoeur approach applied in the Islamic communication is able to be an alternative to delivering a message of Da’wah that is open, inclusive and constructive.Keywords: hermeneutics, Gadamer Ricoeur, analytical techniques, message of da’wa———————————————————————-Artikel ini membahas tentang hermeneutika Gadamer untuk memahami dan menganalisis pesan dakwah, termasuk rasional pentingnya interkonneksi dan integrasi antara teori-teori hermeneutika yang berkembang di Barat dan khazanah keilmuan Islam, khususnya menyangkut pesan dakwah dalam komunikasi Islam. Selain itu, pokok perma–salahan utama yang akan dijawab dalam artikel ini adalah terkait dengan bagaimana perkembangan pemikiran herme–neutik itu sendiri. Penulis berpendapat bahwa pendekatan hermeneutika Gadamer Ricoeur yang diaplikasikan dalam komunikasi Islam ternyata dapat menjadi sebuah alternatif penyampaian pesan dakwah yang terbuka, inklusif dan mengandung pesan yang membangun.Kata Kunci: hermeneutika, Gadamer Ricoeur, teknik analisis, pesan dakwah